Gut Microbiome of a Multiethnic Community Possessed No Predominant Microbiota - Wei Wei Thwe Khine; Anna Hui Ting Teo; Lucas Wee Wei Loong; Jarett Jun Hao Tan; Clarabelle Geok Hui Ang; Winnie Ng; Chuen Neng Lee; Congju Zhu; Quek Choon Lau; Yuan-Kun Lee (Microorganisms, 2021)
With increasing globalisation, various diets from around the world are readily available in global cities. This study aimed to verify if multiethnic dietary habits destabilised the gut microbiome in response to frequent changes, leading to readily colonisation of exogenous microbes. This may have health implications. We profiled Singapore young adults of different ethnicities for dietary habits, faecal type, gut microbiome and cytokine levels. Subjects were challenged with Lactobacillus casei, and corresponding changes in microbiome and cytokines were evaluated. Here, we found that the majority of young adults had normal stool types (73% Bristol Scale Types 3 and 4) and faecal microbiome categorised into three clusters, irrespective of race and gender. Cluster 1 was dominated by Bacteroides, Cluster 2 by Prevotella, while Cluster 3 showed a marginal increase in Blautia, Ruminococaceae and Ruminococcus, without a predominant microbiota. These youngsters in the three faecal microbiome clusters preferred Western high sugary beverages, Southeast Asian plant-rich diet and Asian/Western diets in rotation, respectively. Multiethnic dietary habits (Cluster 3) led to a gut microbiome without predominant microbiota yet demonstrated colonisation resistance to Lactobacillus. Although Bacteroides and Prevotella are reported to be health-promoting but also risk factors for some illnesses, Singapore-style dietary rotation habits may alleviate Bacteroides and Prevotella associated ill effects. Different immunological outcome was observed during consumption of the lactobacilli among the three microbiome clusters.